2001
DOI: 10.1002/1521-3951(200110)227:2<353::aid-pssb353>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Trions in ZnSe-Based Quantum Wells Probed by 50 T Magnetic Fields

Abstract: Singlet and triplet states of negatively charged excitons (trions) in ZnSe/(Zn,Be,Mg)Se quantum wells have been studied by means of photoluminescence in pulsed magnetic fields up to 50 T. Singlet state binding energies, measured for different well widths ranging from 48 to 190 A, show a monotonic increase with growing magnetic fields with a tendency to saturation. This behavior is in qualitative agreement with results of model calculations. Quantitatively, the binding energy of singlet states is underestimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Usually, it is equal to that of neutral excitons 7,13 and its contribution can be accounted for by subtraction of the exciton diamagnetic shift (shift of the center of gravity of the exciton Zeeman doublet) from the trion field dependence.…”
Section: G Coulomb Binding Energy Of the Trion Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, it is equal to that of neutral excitons 7,13 and its contribution can be accounted for by subtraction of the exciton diamagnetic shift (shift of the center of gravity of the exciton Zeeman doublet) from the trion field dependence.…”
Section: G Coulomb Binding Energy Of the Trion Statesmentioning
confidence: 99%
“…In particular, it is shown that additionally to the ground trion state, which is an electron singlet, the trion triplet states are bound at finite magnetic fields. 5,[11][12][13] Two types of triplet states-dark and bright-are studied theoretically [14][15][16][17][18] and experimentally. 7,19,20 In magnetic fields above 20 T the binding energy of the triplet state, which is dark, may exceed the singlet state binding energy, so that the triplet state is the ground state of T − .…”
Section: Introductionmentioning
confidence: 99%
“…spins of two carriers with the same charges (electrons in X − and holes in X + ) in the trion complex are oriented antiparallel. A triplet trion state with parallel orientation of these spins is unbound at zero magnetic field and becomes bound in high fields only [12]. When free carriers are fully polarized by magnetic field the trions can be excited optically only for one circular polarization.…”
Section: Charged Excitons a Identification Of Negatively-and Posmentioning
confidence: 99%
“…Recently the triplet states have attracted considerable attention in GaAs-based QW's [51,52] and in ZnSe-based structures [12]. However, we leave this topic outside the scope of the present paper and concentrate here on the properties of the singlet state.…”
Section: Properties Of Singlet Trion Statesmentioning
confidence: 99%
See 1 more Smart Citation